Reflective impotence in contemporary juvenile dystopia: Conformity as a lesson - Rey Segovia, Ana Clara (Analysis. Journal of Philosophical Research, 2023)
The recent boom of the dystopian genre in today’s audiovisual industry closely echoes the cycle of social protests initiated by social movements like Occupy in the United States or the Spanish 15M —movements led mainly by young people. This is not fortuitous: dystopia has been traditionally associated with a form of denunciation, focused on promoting critical and trasnformative reflection about reality. However, a closer look into some of the most popular dystopian films among young audiences reveals that contemporary dystopias tend to reproduce that which Fisher (2018: 49) called the “reflexive impotence” —impotence that characterizes our time. The narrative structure of these dystopias invites young viewers to a sobering interpretation about the limits of reality, appealing to their conformity with them.